KERENTANAN HIDUP PEREMPUAN PENARIK LANCANG DI KAWASAN PANTAI JAKAT KOTA BENGKULU - Yessilia Osira (Jurusan Sosiologi FISIP UNIB, 2015)
Pulling a sailboat, locally known as nyongsong, is one of informal sector jobs at Pantai Jakat of Bengkulu city. The workers‘ lives depended on the job of fishermen in catching fish, whose income was uncertain. This Study shows that the number of nyongsong woman-workers was increasing, and it was dominated by women aged more than 40 years old with three to seven dependents. Even though initially the motivation of those women in doing their job was just to help their respective family‘s economy, the job is now playing an important role in fulfilling family need. The study shows that the nyongsong may raise vulnerability, namely: a) vulnerability of job and outcome, b) job risk, c) inability to access and manage social guarantee. However, the nyongsong was able to adapt in: a) changing the motivation to help family in fulfilling the family need, b) collecting the fish together with the fishermen, and the result would be divided for two parties, c) producing dried fish, becoming farming laborers, selling vegetables, if there was no job to do.Key words : Sailboat pulling worker, Vulnerability